ETIKA DALAM KOMUNIKASI AKADEMIK: MENGHORMATI RAGAM PANDANGAN SEBAGAI PILAR INTELEKTUALITAS - Fadil Banu Pramana; Windiyani, Sri; Riska, Dara; Hasibuan, M. Lappo; Astuti, Rahayu Fuji (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2025)
Abstract This article explores the importance of respecting diverse perspectives as a fundamental pillar in cultivating inclusive, reflective, and ethical intellectualism. In the context of multicultural societies and academic spaces filled with diverse schools of thought, openness to differing opinions is a key indicator of intellectual maturity. This study employs a descriptive qualitative approach as outlined by Moleong, aiming to understand the subjective meaning behind social phenomena in a holistic manner. The analysis is grounded in recent literature, including academic journals and books published within the last five years. Findings indicate that respecting differing viewpoints functions not only as an ethical norm but also as a crucial mechanism in the development of critical thinking and scientific culture. Multicultural education, intercultural dialogue, and the values of Pancasila play vital roles in internalizing tolerance in both academic and societal contexts. Therefore, respecting diversity of thought is not merely a moral act, but an integral part of a civilized and intellectually engaged process Abstract This article explores the importance of respecting diverse perspectives as a fundamental pillar in cultivating inclusive, reflective, and ethical intellectualism. In the context of multicultural societies and academic spaces filled with diverse schools of thought, openness to differing opinions is a key indicator of intellectual maturity. This study employs a descriptive qualitative approach as outlined by Moleong, aiming to understand the subjective meaning behind social phenomena in a holistic manner. The analysis is grounded in recent literature, including academic journals and books published within the last five years. Findings indicate that respecting differing viewpoints functions not only as an ethical norm but also as a crucial mechanism in the development of critical thinking and scientific culture. Multicultural education, intercultural dialogue, and the values of Pancasila play vital roles in internalizing tolerance in both academic and societal contexts. Therefore, respecting diversity of thought is not merely a moral act, but an integral part of a civilized and intellectually engaged process